Pd:In-Doped TiO2 as a Bifunctional Catalyst for the Photoelectrochemical Oxidation of Paracetamol and Simultaneous Green Hydrogen Production - Sacco, Nicolás Alejandro (2024)
The integration of clean energy generation with wastewater treatment holds promise for addressing both environmental and energy concerns. Focusing on photocatalytic hydrogen production and wastewater treatment, this study introduces PdIn/TiO 2 catalysts for the simultaneous removal of the pharmaceutical contaminant paracetamol (PTM) and hydrogen production. Physicochemical characterization showed a high distribution of Pd and In on the support as well as a high interaction with it. The Pd and In deposition enhance the light absorption capability and significantly improve the hydrogen evolution reaction (HER) in the absence and presence of paracetamol compared to TiO 2. On the other hand, the photoelectroxidation of PTM at TiO 2 and PdIn/TiO 2 follows the full mineralization path and, accordingly, is limited by the adsorption of intermediate species on the electrode surface. Thus, PdIn-doped TiO 2 stands out as a promising photoelectrocatalyst, show-casing enhanced physicochemical properties and superior photoelectrocatalytic performance. This underscores its potential for both environmental remediation and sustainable hydrogen production.